Projeto do aplicativo petmais utilizando a metodologia Design Sprint - Macedo, Jéssica Lopes de (Universidade Federal Rural do Semi-Árido, 2019)
The emergence of mobile computing technology has had a major impact on citizens' daily lives. The ease of access to information and communication that smartphones they brought, encourages the companies to develop more software’s for mobile devices. With the growing application market for the different areas with which users interact daily, it's essential attempt to provide a pleasant experience to them. In this work, will be studied the characteristics of User Interface Design and of User Experience Design, as well as the main methodologies that help to apply them to a project. Therefore, this study aimed to find the methodology more appropriate for the development of the PetMais application project, which aims to help pet owners to manage daily care with them. Among the methodologies studied in this study, the Design Sprint presented better similarity with the objectives of the project, thus being applied to the development of the application.
Monografia
Keywords: Design de interface do usuário; Design de experiência do usuário; Aplicações móveis; Design sprint; User interface design; User experience design; Mobile applications; Design sprint; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO::SISTEMAS DE INFORMACAO